The inequality of finance - Adams, R; Xu, J (Now Publishers, 2023)
Thought leadership in academic finance is more unequal than in other fields. Using data on the top 2% of scientists across all fields from Ioannidis et al. (2019) and Ioannidis et al. (2020), we show that the set of top scientists in finance is less diverse in terms of gender and geography than in economics and other STEM fields. However, top female scientists in finance have relatively more impact than they do in economics and other STEM fields. Women’s average beliefs about the level of brilliance necessary to be in a field have little explanatory power for women’s representation in finance, but men’s beliefs do. Our results suggest that field-specific culture is a higher barrier to women’s advancement in finance than it is in other fields.